The effect of ocean alkalinity enhancement on pelagic bacterial communities: focus points derived from a mesocosm experiment - Antoni, Dominik; Wichels, Antje; Boersma, Maarten; Gerdts, Gunnar (Frontiers in Microbiomes, 2025)
Anthropogenic climate change caused by CO2 emissions forces humanity to reduce the usage of fossil fuels. Along with the task of emission reduction, societies face the task of removing excess CO2 from the atmosphere by using negative emission technologies (NETs). Ocean alkalinity enhancement (OAE) is a proposed NET, aiming at increasing oceanic CO2 uptake through the addition of alkaline substances. This is an anthropogenically accelerated version of rock weathering, a natural global process for atmospheric CO2 regulation. The environmental impacts of OAE remain poorly understood. This study was part of a comprehensive OAE-mesocosm experiment in the North Sea (RETAKE), and focused on the effects of OAE on the pelagic bacterial community during the experiment. We assessed changes in bacterial community structure with 16S rRNA amplicon sequencing and abundance with flow cytometry, to evaluate responses to alkalinity addition. Beta diversity analysis showed that sampling time was the primary driver for community variation, with only marginal structural differences linked to alkalinity treatments. PERMANOVA tests conducted on predictions of functional metabolic pathways of the community revealed significant differences between treatments and baseline controls. A deeper analysis of the identified metabolic pathways revealed little evidence for alkalinity-induced changes. In contrast, total bacterial cell counts were influenced by alkalinity additions, showing delayed abundance peaks at higher concentrations and a non-linear response threshold between 500–750 µmol/L. These dynamics were linked to shifts in chlorophyll concentrations, suggesting an indirect effect of OAE on bacteria mediated by phytoplankton derived resources. This study is one of the first to assess ecological impacts of OAE on bacteria. Our findings highlight a structural resilience of bacterial communities to OAE but also show a quantitative response. By discussing our findings, this study aims to provide focus points, such as a threshold for save levels of alkalinity addition, to direct future research.